GAMBARAN EFIKASI DIRI ORANG TUA DARI ANAK DENGAN KANKER YANG MENDAPAT KEMOTERAPI - Diaspora, Ketut Nanda; Utami, Kadek Cahya; Puspita, Luh Mira (Coping: Community of Publishing in Nursing; Vol 10 No 1 (2022): Februari 2022DO - 10.24843/coping.2022.v10.i01.p04, 2022)
Cancer becomes the main cause of death in children aged 0-19 years. One of the effective treatments to deal with cancer is Chemotherapy. Parents need to have good self-efficacy to be able to accompany the child during chemotherapy in order   the success of therapy. This study aimed to describe the parent’s self-efficacy of children with cancer who got chemotherapy. The design of this study was descriptive quantitative with cross sectional approach. The research sample used amounted to 32 parents at Yayasan Peduli Kanker Anak Bali. Findings of this research showed that the proportion of gender between men and women is the same as 16 respondents (50%), the majority of high school education level as many as 13 respondents (40.6%), there were 35.22 years of respondents in the average age and the average length of time children enter the foundation is for 18.88 months. The average self-efficacy of respondents was 33.09 and belonged to the good category.   Keywords: , Cancer, Parents of Children with Cancer, Self-Efficacy